Targeting hyaluronan for the treatment of pancreatic ductal adenocarcinoma - Norihiro Sato; Xiao-Bo Cheng; Shiro Kohi; Atsuhiro Koga; Keiji Hirata (Elsevier, 2016)
Progression of cancer is often associated with interactions between cancer cells and extracellular matrix (ECM) surrounding them. Increasing evidence has suggested that accumulation of hyaluronan (HA), a major component of ECM, provides a favorable microenvironment for cancer progression. Pancreatic ductal adenocarcinoma (PDAC) is characterized typically by a dense desmoplastic stroma with a large amount of HA, making this molecule as an attractive target for therapy. Several studies have shown efficacy of inhibitors of HA synthesis or signaling for the treatment of PDAC. Recent studies have also demonstrated substantial improvements in the effects of chemotherapy by a targeted depletion of stromal HA in PDAC using an enzymatic agent. Thus, targeting HA has been recognized as a promising therapeutic strategy to treat this highly aggressive neoplasm. In this review article, we summarize our current understanding of the role of HA in the progression of PDAC and discuss possible therapeutic approaches targeting HA.